Disorder eating among urban and rural seconday school children in Selangor, Malaysia / Karen Sharmini Sandanasamy - Karen Sharmini, Sandanasamy (2016)
Disordered eating would be debilitating if it reaches the clinical diagnostic criteria of an eating disorder (i.e. anorexia nervosa and bulimia nervosa). Previous studies in Malaysia have shown a 7% (1995) to 22% (2011) increase in the prevalence of disordered eating. Most prevalence studies comparing rates of disordered eating in urban and rural regions are only conducted abroad. A few that are carried regionally focuses on disordered eating behaviors but not many resorting evidence on its related factors. This study describes the adaptation and validation of the Perceived Sociocultural Pressure Scale (PSPS) and further to assess the prevalence and correlates of disordered eating behaviors among urban and rural secondary school students in Selangor, Malaysia. This two phase study involved the validation of the Bahasa Malaysia version of the Perceived Sociocultural Pressure Scale (PSPS). Confirmatory Factor Analysis (CFA) (n=354) and reliability test were performed (n=70). Phase two comprised a cross-sectional study through multistage sampling of urban and rural schools in Selangor. Providing a sample of 601 students ages between 13 to 16 years. A self-administered questionnaire measuring eating attitudes and behaviors as well as the predictors of disordered eating which was self-esteem, body dissatisfaction and perceived sociocultural pressures (PSP) were assessed. In phase one, overall, items in the scale showed to have high internal consistency (Cronbach α = 0.91). The kappa values in the test-retest reliability of each item ranged from 0.3 to 0.6. In confirmatory factor analysis a 4 factor model yielded a sufficient fit. In phase two, the prevalence of disordered eating was 19.8% (95% CI 16.5, 23.5). More females 20.8% (95% CI 16.6, 25.8) and adolescents who were overweight 26.5% (95 % CI 18.3, 36.7) had disordered eating. Disordered eating was mainly seen among rural schools 25.6% as compared to urban schools 15.2%. The common type of disordered eating practices were binge iv eating 4.10% (95% CI 2.70, 6.00), and excessive exercising, 6.50 %( 95% CI 4.70, 9.00). There were moderate correlations seen among the predictors of disordered eating. Perceived sociocultural pressure to be thin remained to be the significant predictor of disordered eating (OR=4.23 95% CI: 2.89, 6.19). A subgroup analysis between the domains of PSP showed perceived sociocultural pressure (PSP) from family & friends (OR=1.60 95% CI: 1.16, 2.21), PSP media (OR=1.53 95% CI: 1.20, 1.94) and weight teasing (OR=1.39 95% CI: 1.01, 1.90) were significant predictors of disordered eating among these adolescents. The Bahasa Malaysia version of the PSPS has good psychometric properties and can be used to assess sociocultural pressure to be thin among adolescents in Malaysia. Phase two of the study provides support for the importance in targeting adolescent in prevention programs for disordered eating. Public Health Prevention Programs need to take into consideration the full range of disordered eating practices, including binge eating, excessive dieting, consumption of diet pills/laxatives/diuretics as well as excessive exercising as an integrated approach to address the importance of healthy eating in the community.